Features of wisdom and methods in the approach of Imam Hassan al-Askari (Peace Be upon Him) (Journal of the College of Education for Women, 2019)
Wisdom is the separation and distinction between aim in the word and work and the lack thereof in accordance with the knowledge surrounding the arts of science, which reached a thorough understanding of things and put them in the quorum. In this research, I have tried to discern the characteristics of the wisdom of Imam Hassan al-Askari (peace be upon him) and to explain his methods and actions which are indicative of the various facets of wisdom required by the nature of the actions and behavior that he has to deal with. Or future mother.The second topic was devoted to the style of Imam (p) and his wisdom in the situations that necessitated the diversity of methods of dealing such as the method of concealment and the method of reference. .. And the third has been specific to talk about the wisdom of Imam (p) and his outlook for the future outlook and methodology in the prelude to the absence, such as signing the correspondence and send confidential and the absence of sight and agents evidenceThe research concludes with the most important findings.